Effect of Predict-Observe-Explain Instructional Model with Learning Packages of Force on Straight Wire in Magnetic Field with Students’ Matthayom Suksa 6 - Rattanachaya , Aekkapon; Pattanaboonmee , Nakarin; Klunboot, Saengkrit; Emarat, Narumon (Journal of Inclusive and Innovative Education, 2021)
The purpose of this research was to develop students’ understanding of the force on a straight wire in the magnetic field through the Predict-Observe-Explain (POE) teaching method, which included a lesson plan, conceptual test, and demonstration set was designed. The demonstration set was installed by a straight wire connected with a DC power source between the middle of two bar magnets. Then, the movement of straight wire was observed when it was adjusted by the distance of bar magnets and angle of straight wire. After that, it was tested on the experimental group which consisted of 30 students. Compared with the control group that was studied in normal learning about 33 students. The correct conceptual understanding from the control group and experimental group the relationship between the force on a straight wire and bar magnets’ distance was 6.1% and 76.7% respectively, the relationship between the force on a straight wire and angle of a straight wire with the magnetic field were 6.1% and 80.0% respectively. The students’ experimental group got a higher correct conceptual understanding of statistical significance .05 level. The research indicated that using Predict-Observe-Explain (POE) teaching method incorporated with a learning kit can develop the students’ understanding of the force on a straight wire in the magnetic field.